USAHA PIMPINAN DALAM MENINGKATKAN DISPLIN KERJA KARYAWAN PADA PT SENTOSA AGRI PRIMA PALEMBANG - Mulyati, Sri; Kurniati, Kurniati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The title of this research is "Business Leaders in Improving Employee Discipline at PT Sentosa Agri Prima Palembang. The purpose of this study is to find out the application of company regulations in the form of employee work and efforts to improve employee work discipline at PT Sentosa Agri Prima Palembang. This data was collected through a questionnaire with 93 respondents. Based on the primary data processed there are 2 indicators that have been applied in the company and 6 indicators that have not been implemented in the company and the company has made strict rules and sanctions / punishments to achieve company goals and efforts to improve employee work discipline which consists of a negative approach between other disciplinary sanctions, moderate disciplinary sanctions, and severe disciplinary sanctions, then a positive approach includes giving advice, reducing working hours and employee work schedules, and reducing disciplinary action by giving sanctions and disciplining oneself. PT Sentosa Agri Prima should improve the system of implementing discipline in accordance with the Law on work discipline that has not been implemented such as making rules/disciplinary probation periods instead of dismissal, implementing training programs and retraining, holding formal orientations with employees in a relaxed manner and asking for participation in drafting regulations and its application.